Exploring Secondary Students' Algebraic Thinking in Terms of Intuitive Cognitive Style - Rahma Safitri; Masduki Masduki (Jurusan Tadris Matematika UIN Siber Syekh Nurjati Cirebon, 2023)
Algebraic thinking has the important role to improve the students' understanding in solving real-world problems, especially in algebraic forms. The aim of this study is to explore the students' algebraic thinking in terms of intuitive cognitive style. This research used the qualitative approach with case study method. 61 Grade-8 students in one of public secondary schools in Ngawi District, East Java, Indonesia were participated in this study. Three intuitive subjects were selected for interviewed. This study used algebraic thinking test, questionnaires, and interview protocol for collecting the data. Researchers adopted ten questions from TIMSS 2011 8th-Grade to examine the students algebraic thinking abilities. All questions were validated by three experts in mathematics education and piloted before used. In this study, three algebraic thinking components: generalization, analytic thinking, and dynamic thinking were used to analyze the students algebraic thinking abilities. Â The finding showed that the intuitive students can solve number pattern problems using picture and number patterns in generalization component. In analytic thinking component, students can solve problems related to equations using trial-error strategies and substitution methods. The students can also carry out dynamic thinking component about equivalent proportion by determining the median value and proportion concept. Thus, it can be concluded that the intuitive students are able to demonstrate the three algebraic thinking components properly